Correlates of short sleep duration among adolescents. (15th November 2019) - Widome, Rachel; Berger, Aaron T.; Lenk, Kathleen M.; Erickson, Darin J.; Laska, Melissa N.; Iber, Conrad; Kilian, Gudrun; Wahlstrom, Kyla
ABSTRACT: Introduction: Short sleep duration is exceedingly common among adolescents and has implications for healthy youth development. We sought to document associations between adolescents' sleep duration and characteristics of their schedules, behaviors, and wellbeing. Methods: We used data from the baseline wave (9th grade year) of the START study, a cohort of 2134 students in five Minnesota high schools to assess how self‐reported sleep duration was associated with the prevalence of time‐use characteristics (i.e. activity schedules, screen use), sleep‐wake problems (i.e. trouble waking in the morning, falling asleep in class, etc.), and risk of depression. Results: Shorter sleep duration was associated with various behaviors including greater computer/screen time and screen use after bed, a lower probability of doing homework, participation in sports doing chores on school nights, and reporting that it takes at least 20 min to fall asleep on school days (p < 0.05). Suboptimal sleep duration was also associated with a higher probability of all reported sleep‐wake problems as well as higher risk of depressive symptoms (p < 0.05). Conclusions: Given that getting an optimal amount of sleep can protect youth from risk and promote healthy youth development, it is critical that we gain a greater understanding of correlates and consequences of short sleep duration in order to develop a sleep‐friendly culture for youth.